URGENSI PENERAPAN KEPATUHAN SYARIAH PADA PERBANKAN SYARIAH - Dwi Kusumaningrum; Mohammad Yusrifal; Nabilatul Mumtazah P.H; Yahya Fuad (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
The results of Bank Indonesia's research report that customers who use Islamic banking services have doubts about the consistency of the implementation of sharia principles. As a result, some have a tendency to stop being customers. Compliance and suitability of Islamic banks to Islamic principles are often questioned by customers. It implicitly shows that the Islamic banking application has paid less attention to the principles of sharia. Using qualitative research methods with a library research approach. The results of this study prove that Sharia compliance is very important to increase customer trust / confidence in Islamic Banks. Meanwhile, the factor for increasing customer trust / confidence in Islamic banks by implementing sharia governance is because it can increase confidence / trust in the long term and increase customer loyalty.